2019
DOI: 10.18502/tim.v4i3.1677
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Enseraf-E- Tabiat (Nature Distraction) in Disease Treatment

Abstract: This article is a Letter to the Editor and does not include an Abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Meng et al found that, although Traditional Chinese medicine is widely recognized as effective in treating chronic diseases, some TCM therapies like blowing air to the ear, nose insufflating therapy, acupuncture, and moxibustion are potent in many acute and urgent medical conditions [ 40 ]. In PM, Nature as an innate power controls all aspects of the body [ 18 , 57 ]. Deviating Nature by phlebotomy and wet cupping, two common manual interventions used in PM, plays an important role in protecting the principal organs of the body by purifying the blood [ 46 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meng et al found that, although Traditional Chinese medicine is widely recognized as effective in treating chronic diseases, some TCM therapies like blowing air to the ear, nose insufflating therapy, acupuncture, and moxibustion are potent in many acute and urgent medical conditions [ 40 ]. In PM, Nature as an innate power controls all aspects of the body [ 18 , 57 ]. Deviating Nature by phlebotomy and wet cupping, two common manual interventions used in PM, plays an important role in protecting the principal organs of the body by purifying the blood [ 46 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%